Study on the Optimal Treatment Condition Control of Photothermal Therapy under Various Cooling Time Ratios of Lasers - Kim, Donghyuk; Kim, Hyunjung (International Journal of Molecular Sciences, 2022)
Photothermal therapy is a treatment technique that has attracted attention as an alternative to conventional surgical techniques. It is based on the photothermal effect, wherein light energy is converted into thermal energy, and facilitates rapid recovery after treatment. This study employed various laser irradiation conditions and presented conditions with the optimal treatment effects through a numerical analysis based on heat transfer. A skin layer comprising four stages containing squamous cell carcinoma was targeted, and the treatment effect was confirmed by varying the heating conditions of the laser and volume fraction of gold nanoparticles. The therapeutic effect was confirmed through both the apoptosis retention ratio, which quantitatively estimated the degree of maintenance of the apoptosis temperature range within the tumor, and the thermal hazard retention value, which quantitatively calculates the amount of thermal damage to the surrounding normal tissues. Finally, the optimal treatment conditions were determined based on the laser intensity, cooling time ratio, and volume fraction of injected gold nanoparticles through numerical analysis.
Keywords: Gold; Hyperthermia, Induced; Lasers; Metal Nanoparticles; Photothermal Therapy; apoptosis; cooling time ratio; gold nanoparticles; heat transfer; Monte Carlo method; NIR laser; numerical; photothermal therapy; squamous cell carcinoma; thermal damage